Spin-dependent holed delocalization enhancement by bandfilling effects in degenerate asymmetric double quantum wells - Kemerink, Martijn; Koenraad, Paulus M.; Wolter, Joachim H.; Christianen, Peter; Geim, A. K.; Parlangeli, A.; Maan, J. C.; Henini, Mohamed (Superlattices and microstructures, 2002)
We studied the wavefunctions and energy positions of the confined states in the valance band in an asymmetric double quantum well. We found these to be extremely sensitive to both the carrier density and the height of the confining barriers, which allows us to control the so-called ‘Spin Dependent Hole Delocalization’. The theoretical results are shown to be in excellent agreement with experiments.
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.12.2019